(untitled) (Journal of Dhaka National Medical College & Hospital, 2015)
Tuberculosis (TB) is a rare disease in developed countries although it is endemic in developing countries, especially in Africa and Asia. Involvement of the sternum by microbacterium tuberculosis is rare. Thus diagnosis of sterna TB is not often considered particularly in developed countries. Here we report a case who present with swelling of the sternum in UK but ultimately diagnosed as a case of primary sterna TB in Bangladesh. J. Dhaka National Med. Coll. Hos. 2015; 21 (01): 55-57